2011
DOI: 10.1177/000313481107700507
|View full text |Cite
|
Sign up to set email alerts
|

Article Commentary: Aberrant Hepatic Arterial Anatomy and the Whipple Procedure: Lessons Learned

Abstract: Appreciation and study of hepatic arterial anatomical variability is essential to the performance of a pancreaticoduodenectomy to avoid surgical complications such as bleeding, hepatic ischemia/failure, and anastomotic leak/stricture. Awareness of this variability permits the surgeon to adapt the surgical technique to deal with anomalies identified preoperatively or intraoperatively thereby preventing unnecessary surgical morbidity and mortality. The objective of our study is to provide a comprehensive review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…For instance, most of the blood supply to the extrahepatic biliary tree comes from the RHA or rRHA. Accidental injury to these arteries during hepatic surgery might lead to ischaemia of the biliary anastomosis. Ishigami and colleagues reported that variant hepatic artery anatomy in a liver transplant recipient increased the risk of hepatic artery complications after transplantation by 18 per cent.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, most of the blood supply to the extrahepatic biliary tree comes from the RHA or rRHA. Accidental injury to these arteries during hepatic surgery might lead to ischaemia of the biliary anastomosis. Ishigami and colleagues reported that variant hepatic artery anatomy in a liver transplant recipient increased the risk of hepatic artery complications after transplantation by 18 per cent.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of an aberrant RHA has been shown in many studies not to impact outcomes in open PD . Descriptions of the impacts of other less common arterial anomalies on PD are mostly limited to review articles and small case series or reports . This is the first study to examine the impact of HAAs on the outcomes of minimally invasive PD.…”
Section: Discussionmentioning
confidence: 99%
“…6 Of note, angiography has been replaced by angio-MRI or angio-CT to assess vascularization. 7 In particular, angio-CT is accurate LGA left gastric artery, a LHA aberrant left hepatic artery, P pancreas, a RHA aberrant right hepatic artery, VP portal vein, VC vena cava, SMA superior mesenteric artery to predict resectability of pancreas head tumors in 80 % of cases. 8 The other interesting feature of this case is the prepancreatic course of the aRHA, instead of the classically described retropancreatic and latero-cave course.…”
Section: Discussionmentioning
confidence: 99%
“…9 There is however a risk of long-term biliary ischemia, or even necrosis of a hepatic segment, or a risk of bile leak on the biliojejunostomy if the vascular supply is due to the aRHA. 7 On the other hand, this risk is still debated. 7 Others propose the reimplantation of the aRHA on the gastroduodenal artery to limit the ischemic risk, but this technique has been claimed to increase the risk of lethal hemorrhage in case of postoperative pancreatic fistula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation